2015
DOI: 10.21608/ejnf.2015.104368
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Different Levels of Dried Distiller's Grainswith Solubles as a Replacement for Soybean Meal and Portion of the Corn in a Growing and Finishing Baffalo Calves Diet

Abstract: ighty growing buffalo calves, 14-16 months old, with an average weight of 202 kg, were divided, randomly, into four equal experimental groups, (20 calves each), and used to investigate the effect of replacing 0%, 10%, 20% and 30% of soybean and yellow corn by dried distiller's grains with soluble (DDGS) in total mixed rations (TMR) (1,2,3 and 4, respectively). The experimental diets were nearly similar in crude protein (CP) (iso-nitrogenous) and total digestible nutrients (TDN) (iso-caloric). All animals were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 21 publications
(13 reference statements)
3
6
0
Order By: Relevance
“…Increasing feed intake of animals fed ration containing DDGS (ration D) might be attributed not only higher digestibility coefficients of all nutrients of these ration, but also higher it's feeding values such as TDN, DCP, DE and ME (table 3). These results were agreement with those reported by Etman et al (2011& 2014 and El-Shinnawy et al (2015).…”
Section: Average Daily Feed Conversion Rate and Feed Efficiency Of Exsupporting
confidence: 94%
See 1 more Smart Citation
“…Increasing feed intake of animals fed ration containing DDGS (ration D) might be attributed not only higher digestibility coefficients of all nutrients of these ration, but also higher it's feeding values such as TDN, DCP, DE and ME (table 3). These results were agreement with those reported by Etman et al (2011& 2014 and El-Shinnawy et al (2015).…”
Section: Average Daily Feed Conversion Rate and Feed Efficiency Of Exsupporting
confidence: 94%
“…On the other hand, feed utilization as kg TDN/ kg actual or 4% FCM yield found to be most efficient for animals fed ration C (containing soybean meal) with no significant difference, while feed efficiency as Kg DCP/ Kg actual or 4% FCM yield was almost equal among different experimental groups without significant differences. Better feed efficiency with animals fed ration containing DDGS was reported by Etman et al (2014) and El-Shinnawy et al (2015).Generally, using DDGS in rations tended to increase milk yield and improve feed utilization efficiency.…”
Section: Average Daily Feed Conversion Rate and Feed Efficiency Of Exmentioning
confidence: 84%
“…Moreover, Leupp et. al., (2009) observed that increasing and improving of digestibility coefficients and nutritive values of ration containing DDGS might be attributed to higher availability of nutrient contents of DDGS.Generally, ration D(containing DDGS) appeared to have higher nutrient digestibility coefficients and feeding value than the other rations as reported by El-Shinnawy et. al.,(2015).…”
Section: Digestibility Coefficients and Feeding Valuesmentioning
confidence: 84%
“…Generally, the better feed efficiency with animals fed ration D (containing DDGs) was agreement with those reported by Etman et. al., (2014aand 2018) and El-Shinnawy et. al.…”
Section: Average Feed Intake Daily Gain and Feed Efficiencymentioning
confidence: 96%
See 1 more Smart Citation